Review of Attfield, Robin, Applied Ethics: An Introduction (Polity: Cambridge, UK, 2022, and Hoboken, NJ, 2023). - Rebekah Humphreys (Bangladesh Journal of Bioethics)
This review provides a chapter-by-chapter outline and critical commentary of Robin Attfield’s Applied Ethics: An Introduction, published by Polity. Attfield’s voice as a highly experienced teacher, as well as an expert in applied ethics, comes through crystal clear in this important and insightful book, guiding students and teachers through the myriad of ethical arguments in central topics in applied ethics, whilst encouraging the depth of thought that students need to become ethicists in their own right. The result of all this is a book that will undoubtedly serve as a vital resource for anyone interested in studying ethics in practice. Indeed, the style of writing that Attfield is well-known for is epitomised in this book, making it a ‘go to’ text or the first port of call for teachers and students of ethics alike.